Evaluation of performance, combustion and emission characteristics of blends of Sesame Biodiesel in a single cylinder Diesel Engine: An experimental approach - Karn, Rupesh Lal; Sharma, Shahil; Maharjan, Lasta; Bajagain, Gagin; Jyakhwo, Samjhana; Subedi, Sushila; Palikhel, Laxman (Journal of Innovations in Engineering Education, 2025)
The study examines the performance, combustion, and emission characteristics of a diesel engine fueled with sesame biodiesel methyl ester (SBME)–diesel blends containing 0–100% SBME by volume (i.e., 0%, 10%, 20%, 30%, and 40% SBME blended with conventional diesel. The findings highlight significant improvements in combustion efficiency and emissions reduction with SBME compared to diesel, with 20 SBME emerging as the optimal blend. For 20 SBME, Brake Thermal Efficiency improves by 9.57%, and specific fuel consumption decreases by 7.94%, while Mechanical Efficiency increases by 0.618%. Indicated Power rises for 10, 30, and 40 SBME but slightly declines for 20 SBME by 0.66%. Emissions analysis shows reductions in CO₂, NO, and HC emissions for 10 and 20 SBME, with decreases of up to 3.5%, 19.18%, and 36.55%, respectively, while higher blends result in increased emissions. Combustion analysis reveals enhanced Cylinder Pressure Maximum (CPM) and Net Heat Release (NHR) for 20 and 30 SBME, alongside a reduction in Cumulative Heat Release (CHR) across all blends. Additionally, exhaust gas temperature and heat loss through radiation increase at higher loads. These results demonstrate that 20 SBME offers a balanced improvement in engine performance, combustion characteristics, and environmental impact, making it a viable alternative to conventional diesel.